Downregulation of Protein Tyrosine Phosphatase Receptor Type R Accounts for the Progression of Hirschsprung Disease - Tian, Jiao; Zeng, Cheng; Tian, Zhen; Lin, Yan; Wang, Baoxi; Pan, Yongkang; Shu, Zhen; Jiang, Xun (Frontiers in Molecular Neuroscience, 2019)
Hirschsprung disease (HSCR) is a common developmental disorder of the enteric nervous system (ENS). However, the disease mechanisms have not been fully elucidated. To better understand the etiology of HSCR, the role and mechanism of HSCR associated PTPRR (protein tyrosine phosphatase receptor-type R) in the multipotency of ENS progenitors and ENS development were explored. In the present study, the downregulated PTPRR expression in HSCR was reflected by microarray and validated by real-time PCR analyses. Moreover, PTPRR protein was mainly expressed in the cytoplasmic area of primary cultured ENS progenitors (Enteric neural crest cells, ENCCs) and significantly decreased after differentiation induction, which implies the anti-differentiation role in ENCCs. Further study employed an adenovirus transfection system. After genetic modulation, the ENCCs maintained undifferentiated patterns even in GDNF (Glial cell-line derived neurotrophic factor)-mediated directional differentiation, as well as significantly increased EdU positive immunofluorescence in the PTPRR overexpressing group while the development of the ENS was stunted in the PTPRR knockdown fetal gut. Moreover, the expression of ERK1/2 activated by GDNF was significantly decreased as reflected by western-blot or immunofluorescence analyses after genetic modulation in the PTPRR overexpressing group, which suggests the potential mechanism in regulating the MAPK/ERK1/2 pathway. Taken together, These data support the idea that PTPRR may ensure a certain number of neural precursor cells by inhibiting ENCC overt differentiation and maintaining ENCC proliferation, which is considered to be the multipotency of ENCCs, and eventually participate in the development of the ENS, and establish PTPRR protein as negative regulator of MAPK/ERK1/2 signaling cascades in neuronal differentiation and demonstrate their involvement in the pathophysiology of HSCR.